Developing mathematical model for diurnal dynamics of photosynthesis in Saccharum officinarum responsive to different irrigation and silicon application - Krishan K. Verma; Kai-Chao Wu; Chhedi Lal Verma; Dong-Mei Li; Mukesh Kumar Malviya; Rajesh Kumar Singh; Pratiksha Singh; Gan-Lin Chen; Xiu Peng Song; Yang Rui Li (PeerJ, 2020)
In the dynamic era of climate change, agricultural farming systems are facing various unprecedented problems worldwide. Drought stress is one of the serious abiotic stresses that hinder the growth potential and crop productivity. Silicon (Si) can improve crop yield by enhancing the efficiency of inputs and reducing relevant losses. As a quasi-essential element and the 2nd most abundant element in the Earth’s crust, Si is utilized by plants and applied exogenously to combat drought stress and improve plant performance by increasing physiological, cellular and molecular responses. However, the physiological mechanisms that respond to water stress are still not well defined in Saccharum officinarum plants. To the best of our knowledge, the dynamics of photosynthesis responsive to different exogenous Si levels in Saccharum officinarum has not been reported to date. The current experiment was carried out to assess the protective role of Si in plant growth and photosynthetic responses in Saccharum officinarum under water stress conditions. Saccharum officinarum cv. ‘GT 42’ plants were subjected to drought stress conditions (80–75%, 55–50% and 35–30% of soil moisture) after ten weeks of normal growth, followed by the soil irrigation of Si (0, 100, 300 and 500 mg L−1) for 8 weeks. The results indicated that Si addition mitigated the inhibition in Saccharum officinarum growth and photosynthesis, and improved biomass accumulation during water stress. The photosynthetic responses (photosynthesis, transpiration and stomatal conductance) were found down-regulated under water stress, and it was significantly enhanced by Si application. No phytotoxic effects were monitored even at excess (500 mg L−1). Soil irrigation of 300 mg L−1 of Si was more effective as 100 and 500 mg L−1 under water stress condition. It is concluded that the stress in Saccharum officinarum plants applied with Si was alleviated by improving plant fitness, photosynthetic capacity and biomass accumulation as compared with the control. Thus, this study offers new information towards the assessment of growth, biomass accumulation and physiological changes related to water stress with Si application in plants.